Enhanced Magnetization in CoFe2O4 Through Hydrogen Doping. (10th February 2023) - Li, Zhuolu; Lyu, Yingjie; Ran, Zhao; Wang, Yujia; Zhang, Yang; Lu, Nianpeng; Wang, Meng; Sassi, Michel; Ha, Thai Duy; T. N'Diaye, Alpha; Shafer, Padraic; Pearce, Carolyn; et al.
Abstract: Magnetic spinel oxides have attracted extensive research interest due to their rich physics and wide range of applications. However, these materials invariably suffer suppressed magnetization, due to structural imperfections (e.g., disorder, anti‐site defects, etc.). Herein, a dramatic enhanced magnetization is obtained with an increasement of 5 µ B /u.c in CoFe2 O4 (CFO) through ionic liquid gating induced hydrogen doping. The intercalated hydrogen ions lead to both distinct lattice expansion of ≈0.7% and notable Fe valence state reduction through electron doping, in which ≈17% Fe 3+ is reduced into Fe 2+ . These facts collectively trigger a site‐specific spin‐flip on tetrahedrally coordinated Co 2+ sites that enhances the net ferrimagnetic moment nearly to its theoretical maximum for perfect CFO. Abstract : Magnetic spinel oxides typically suffer suppressed magnetization due to structural imperfections. This work demonstrates a dramatic enhanced magnetization in CoFe2 O4 through ionic liquid gating induced hydrogenation. The intercalated hydrogen ions lead to both notable valence reduction and distinct lattice expansion, which collectively trigger a site‐specific spin‐flip on tetrahedrally coordinated Co ions and reclaim effectively the total magnetization toward theoretical value.